2013
DOI: 10.1186/1743-0003-10-101
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming for balance training of elderly: state of the art and future developments

Abstract: Fall injuries are responsible for physical dysfunction, significant disability, and loss of independence among elderly. Poor postural control is one of the major risk factors for falling but can be trained in fall prevention programs. These however suffer from low therapy adherence, particularly if prevention is the goal. To provide a fun and motivating training environment for elderly, exercise games, or exergames, have been studied as balance training tools in the past years. The present paper reviews the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(162 citation statements)
references
References 81 publications
4
141
0
17
Order By: Relevance
“…These results are consistent with other studies of different interventions with exergame (Duque et al, 2013;Maillot et al, 2012;Padala et al, 2012;Pichierri et al, 2012;Schoene et al, 2013;Van Diest, Lamoth, Stegenga, Verkerke, & Postema, 2013) and independent of how the balance was evaluated. In some studies (Padala et al, 2012;Van Diest et al, 2013) the interventions were carried out by means of balance games, using a Wii balance board. Padala et al (2012) compared the results of the exergame (balance games) to an active control group, as in this study, and showed that the results for the TUG test were similar to the results of the group that performed aerobic walking exercise.…”
Section: Jpes ®supporting
confidence: 82%
“…These results are consistent with other studies of different interventions with exergame (Duque et al, 2013;Maillot et al, 2012;Padala et al, 2012;Pichierri et al, 2012;Schoene et al, 2013;Van Diest, Lamoth, Stegenga, Verkerke, & Postema, 2013) and independent of how the balance was evaluated. In some studies (Padala et al, 2012;Van Diest et al, 2013) the interventions were carried out by means of balance games, using a Wii balance board. Padala et al (2012) compared the results of the exergame (balance games) to an active control group, as in this study, and showed that the results for the TUG test were similar to the results of the group that performed aerobic walking exercise.…”
Section: Jpes ®supporting
confidence: 82%
“…Exercise through video games, socalled exergames, is used progressively more to increase physical activity and improve health and physical function in older adults (1,(3)(4)(5), and there is growing interest in using exergames as a potential rehabilitation tool to facilitate specific exercises in different clinical groups (6)(7)(8). Studies suggest that exergaming promotes improvements in mobility (9,10), muscular strength of the lower limbs (11), balance control (2,12,13), and cognition (14) in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, this literature review clearly suggests that most researchers were interested in the improvement of fitness because physical inactivity among adults (e.g., Bonetti, Drury, Danoff, & Miller, 2010;Diest et al, 2013) and children is a major contributor to diseases associated with obesity (World Health Organization, 2010). There was a great number of studies that have investigated AVGs participation in PA and its positive effects in reducing the risk of obesity (e.g., Maloney, Threlkeld, & Cook, 2012;Goersch et al, 2013), hypertension (e.g., Chen & Wilkosz, 2014), congestive heart failure (e.g., Klompstra, Jaarsma, & Strömberg, 2014;Tripette et al, 2014), atherosclerosis (e.g., Laufer, Dar, & Kodesh, 2014) and cardiovascular disease (e.g., Thompson, Gordon, & Pescatello, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature shows that AVGs are considered a valuable additional component to programs enhancing general health, physical fitness and psychomotor functioning (Gioftsidou et al, 2013;Peng, Crouse, & Lin, 2013;Vernadakis et al, 2012) as well as therapy and rehabilitation procedures (Klompstra, Jaarsma, & Strömberg, 2013;Sin & Lee, 2013;Van Diest, Lamoth, Stegenga, Verkerke, & Postema, 2013). However, there is still very limited empirical evidence that exergames can facilitate motor skill acquisition, or can provide an alternative to motor skill enhancing physical activity (Barnett, Hinkley, Okely, Hesketh, & Salmon, 2012;Papastergiou, 2009).…”
Section: Introductionmentioning
confidence: 99%